Evaluación técnico financiera del sistema de levantamiento artificial para un pozo piloto en yacimiento no convencional ubicado en el Campo Llanura (2017)
The present work of degree, performs the evaluation of the systems of artificial lift, to choose the one that is considered suitable to be used in the production of unconventional hydrocarbons in the Pilot Well of the Plain Field in the Mid Valley Basin of Magdalena. The scope of this project was field application level, where the implementation and subsequent testing of the selected survey system is done.